1991
DOI: 10.1016/0014-5793(91)80481-h
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against synthetic amphipathic helical sequences of surfactant protein SP‐B detect a conformational change in the native protein

Abstract: Syntltetic peptides based on the native human sequen¢~ of surfactant protein B have I~,en used to generate polyclonal monospecific antibodies against specific segments of the native SP-B protein, Circular dichroism analysis or the synthr.tic p, have a dominant helical content in structure promotinll environments and tensiometric measurements indicate these peptides lower surface tension at air=water interfaces implyin~ that they contain amphipathic alpha helical motifs, Antibodies directed aB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 15 publications
2
22
0
Order By: Relevance
“…The "blue" shift in the fluorescence maximum for SP-BI-2s is most likely due to peptide aggregation in PBS. Previous CD studies of SP-B,-,, in PBS indicated a concentration-dependent change in structure typical of peptide-self association (Fan et al, 1991). This aggregation phenomenon is further indicated by the characteristic ESR spectral broadening for SP-BT-,, in PBS (see above), which suggested a significant population of peptide aggregates in solution.…”
Section: Endogenous Tryptophan Fluorescence Of Sp-bi_23 In Structure-mentioning
confidence: 73%
See 3 more Smart Citations
“…The "blue" shift in the fluorescence maximum for SP-BI-2s is most likely due to peptide aggregation in PBS. Previous CD studies of SP-B,-,, in PBS indicated a concentration-dependent change in structure typical of peptide-self association (Fan et al, 1991). This aggregation phenomenon is further indicated by the characteristic ESR spectral broadening for SP-BT-,, in PBS (see above), which suggested a significant population of peptide aggregates in solution.…”
Section: Endogenous Tryptophan Fluorescence Of Sp-bi_23 In Structure-mentioning
confidence: 73%
“…These results complement a n earlier immunologic study (Longo et al, 1992) of SP-BI-,, bound to liposomes that also provided information on the exposure of protein domains to the aqueous buffer. Antibodies raised to the amphipathic helical region encompassing SP-B residues Cys-8 to Gly-25 (Fan et al, 1991) showed that this sequence is accessible to the bulk aqueous solvent with SP-B,_,, bound to surfactant liposomes (Longo et al, 1992). In this context, it should be noted that our polarized FTIR measurements indicate that the helical axis (SP-B residues 8-25) inserts in surfactant lipids at an oblique angle with respect to the surface of the film (Table 1).…”
Section: Sp-b- Topography In Membrane-mimic Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…This protein is a major component of the lung surfactant together with other lipid-binding proteins and phospholipids. It is interesting to note that a synthetic peptide (Leu4"pLeu66 of SP-B), corresponding approximately to the position of sapB-18 in saposin B, also adopts an a-helical conformation and binds lipids [23]. This similarity between SP-B and saposin B suggests that these two similar proteins may bind lipids using similar structural elements and mechanisms.…”
Section: Resultsmentioning
confidence: 99%